2020
DOI: 10.1073/pnas.2005013117
|View full text |Cite
|
Sign up to set email alerts
|

Overparameterized neural networks implement associative memory

Abstract: Identifying computational mechanisms for memorization and retrieval of data is a long-standing problem at the intersection of machine learning and neuroscience. Our main finding is that standard overparameterized deep neural networks trained using standard optimization methods implement such a mechanism for real-valued data. We provide empirical evidence that 1) overparameterized autoencoders store training samples as attractors and thus iterating the learned map leads to sample recovery, and that 2) the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 22 publications
(26 reference statements)
0
42
0
Order By: Relevance
“…While autoencoders and other generative models have been used for computing signatures of perturbations also in other works 39,40 , these works have used autoencoders in the standard way to obtain a lower-dimensional embedding of the data. Motivated by our recent work which, quite counter-intuitively, described various benefits of using autoencoders to learn a latent representation of the data that is higher-dimensional than the original space 41 , we found that overparameterized autoencoders not only led to the better Protein coding genes SARS-CoV-2 L1000 Fig. 3 Mining FDA-approved drugs by correlating disease and drug signatures using an overparameterized autoencoder embedding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While autoencoders and other generative models have been used for computing signatures of perturbations also in other works 39,40 , these works have used autoencoders in the standard way to obtain a lower-dimensional embedding of the data. Motivated by our recent work which, quite counter-intuitively, described various benefits of using autoencoders to learn a latent representation of the data that is higher-dimensional than the original space 41 , we found that overparameterized autoencoders not only led to the better Protein coding genes SARS-CoV-2 L1000 Fig. 3 Mining FDA-approved drugs by correlating disease and drug signatures using an overparameterized autoencoder embedding.…”
Section: Resultsmentioning
confidence: 99%
“…First, in order to ensure that the CMap database, which measures expression using 1000 representative genes, would be useful in the context of SARS-CoV-2, we validated that the intersection of these genes with the SARS-CoV-2 differentially expressed genes was significant. Second, to establish drug signatures based on the CMap database, we employed a particular autoencoder framework 41 . Rather unintuitively, we showed that using an overparameterized autoencoder, i.e., by using an autoencoder not to perform dimension reduction as usual but to instead embed the data into a higher-dimensional space, aligned the drug signatures across different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we used the same code to analyze the six influenza studies (with rank between 6-9) and the HIV-1 Catnap dataset containing hundreds of studies (with rank 23). Further refinements to our approach could incorporate side information such as virus sequence (Radhakrishnan et al, 2021) or use tensor factorization to decompose higher-order data (Liu & Moitra, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…One line of enquiry is interpreting depth recursively. Indeed, in certain settings increasing the depth manifests similarly to iterating a map given by a shallow network (Radhakrishnan, Belkin and Uhler 2020). Furthermore, fixed points of such iterations have been proposed as an alternative to deep networks, with some success (Bai, Kolter and Koltun 2019).…”
Section: Are Deep Neural Network Kernel Machines?mentioning
confidence: 99%